Incidence, diagnostic criteria and outcome following ventriculoperitoneal shunting of idiopathic normal pressure hydrocephalus in a memory clinic population: a prospective observational cross-sectional and cohort study - George Razay; Melissa Wimmer; Iain Robertson (BMJ Open)
Objective To evaluate diagnostic criteria for idiopathic normal pressure hydrocephalus (INPH) among patients with memory impairment, and to estimate the incidence of INPH.Design Prospective observational cross-section and cohort study of diagnostic accuracy.Setting Memory Disorders Clinic following referral by the medical practitioners.Participants 408 consecutive patients enrolled 2010–2014.Outcome measures Reference diagnostic test was the clinical judgement of an experienced specialist based on the presence of cognitive impairment and/or balance and gait disorders in the presence of dilated ventricles. Mini-Mental State Examination (MMSE), Tinetti balance and gait tests were performed before and 12 months after ventriculoperitoneal shunt surgery. The association between reference diagnosis, clinical and brain CT scan measurements was estimated by multivariate Poisson regression. Triage index diagnostic test scores were calculated from the regression coefficients, with diagnostic thresholds selected using receiver operating characteristic analysis.Results The presence of balance and/or gait disorders, especially fear of falling, difficulty standing on toes/heals, urinary disturbances, ventriculomegaly with Evans ratio greater than Combined Diagnostic Threshold (0.377-{Maximum width of posterior horns*0.0054}), strongly predict the diagnosis of INPH; while hallucinations and/or delusions and forgetfulness reduce the likelihood of the diagnosis. This triage index test had high sensitivity (95.2%) and specificity (91.7%). 62 of 408 (15%) participants with cognitive impairment had INPH, an incidence of 11.9/100 000/year and 120/100 000/year over 75 years. 96% of participants following shunting, compared with 45% of the non-shunted, improved by over 25% of available measurable improvement in either MMSE or balance/gait scores (51% difference; 95% CI 28% to 74%; p<0.001), and 56% vs 5% improved by over 50% of maximum in both (51% difference; 95% CI 30% to 73%; p<0.001).Conclusion The triage index test score is a simple tool that may be useful for physicians to identify INPH diagnoses and need for referral for shunt surgery, which may improve cognitive, balance and gait functioning.